Cell-based medicinal products approved in the European Union: current evidence and perspectives - Stefania Bellino; Anna La Salvia; Maria Francesca Cometa; Rosanna Botta (Frontiers Media S.A., 2023)
Advanced Therapy Medicinal Products (ATMPs) are innovative clinical treatments exploiting the pharmacological, immunological, or metabolic properties of cells and/or gene(s) with the aim to restore, correct, or modify a biological function in the recipient. ATMPs are heterogeneous medicinal products, developed mainly as individualized and patient-specific treatments, and represent new opportunities for diseases characterized by a high-unmet medical need, including rare, genetic and neurodegenerative disorders, haematological malignancies, cancer, autoimmune, inflammatory and orthopaedic conditions. Into the European Union (EU) market, the first ATMP has been launched in 2009 and, to date, a total of 24 ATMPs have been approved. This review aims at reporting on current evidence of cell-based therapies authorized in the EU, including Somatic Cell Therapies, Tissue Engineering Products, and Cell-based Gene Therapy Products as Chimeric Antigen Receptor (CAR) T-cells, focusing on the evaluation of efficacy and safety in clinical trials and real-world settings. Despite cell-based therapy representing a substantial promise for patients with very limited treatment options, some limitations for its widespread use in the clinical setting remain, including restricted indications, highly complex manufacturing processes, elevated production costs, the lability of cellular products over time, and the potential safety concerns related to the intrinsic characteristics of living cells, including the risk of severe or life-threatening toxicities, such as CAR-T induced neurotoxicity and cytokine release syndrome (CRS). Although encouraging findings support the clinical use of ATMPs, additional data, comparative studies with a long-term follow-up, and wider real-world evidences are needed to provide further insights into their efficacy and safety profiles.